Enhancing the Market Appeal of ’Pak Boss’ Rice Bran Cereal Through Visual Packaging Design - Yasdaniar, Marsha Mafisa; Dwitasari, Putri; Alamin, Rabendra Yudistira; Sayatman, Sayatman (VCD, 2025)
Indonesia, as the second-largest rice producer in Asia and third globally, generates a significant amount of rice bran as a by product of the rice milling process. Despite its high nutritional value and potential for human consumption, rice bran remains underutilized. "Pak Boss," a local brand, addresses this gap by processing rice bran into a healthy cereal product. However, the brand faces key challenges in market acceptance, primarily due to limited public awareness and ineffective packaging.This study focuses on the redesign of Pak Boss’s packaging to enhance its visual communication and market appeal. The problem lies not only in consumer unfamiliarity with bran cereal but also in the lack of packaging that effectively conveys the product’s benefits and identity. Employing a combination of methods observation, literature review, surveys, in-depth interviews, experimental design, and user testing using the VIEW model (Visibility, Information, Emotional Appeal, and Workability) this design approach aims to solve these issues. The outcome seeks to position packaging not merely as a container, but as a strategic medium for branding, education, and consumer engagement. Through improved visual design, the study aims to elevate the public perception of bran cereal and strengthen its position as a nutritious, locallysourced product in the competitive cereal market.